Relative high frequency of the c.255delA parkin gene mutation in Spanish patients with autosomal recessive parkinsonism. Issue 5 (1st November 2002) - Muñoz, E; Tolosa, E; Pastor, P; Martí, M J; Valldeoriola, F; Campdelacreu, J; Oliva, R
Abstract : Background: Autosomal recessive juvenile parkinsonism is a neurodegenerative disorder associated with mutations in the parkin gene. Objectives: To search for the presence of parkin gene mutations in Spanish patients with Parkinson's disease (PD) and characterise the phenotype associated with these mutations. Methods: Thirty seven PD patients with either early onset or autosomal recessive pattern of inheritance were selected for genetic study. Results: Mutations were identified in seven index patients (19%). Homozygous mutations were detected in six patients and a heterozygous mutation in one. The age at onset was lower in patients with mutations than in patients without mutations. Dystonia at onset was present in two patients with parkin gene mutations. The disease began in two patients with postural tremor in the upper limbs mimicking essential tremor. Four patients exhibited a long term response to dopamine agonists. The c.255delA mutation was identified in four unrelated families. This is a frameshift mutation leading to protein truncation. Conclusions: Parkin gene mutations are present in Spanish patients with early onset and/or an autosomal recessive parkinsonism. The c.255delA is the most frequent mutation found, suggesting a relative high prevalence in the Spanish population.